The dates of Westwood’s Mecoptera (Insecta) publications reexamined and further corrected - Somma, Louis A. (Zootaxa, 2012)
In a recent issue of Zootaxa (Somma 2011), I corrected the publication dates for one genus and 14 species of Mecoptera (1 choristid, 4 bittacids, and 9 panorpids) and resurrected Panorpa confusa Westwood, 1841, which made Panorpa rufescens Rambur, 1842, a junior synonym of P. confusa. Additionally, I provided a nomenclatural and taxonomic summary for these taxa, and a publication history for all of Westwood’s related publications. However, there were several inaccuracies to the dates I applied to these publications that I herein correct.